Preparation method and application of perovskite oxide nanofiber for anchoring Ru monatomic

By anchoring Ru single atoms on perovskite oxide nanofibers to form Ru-O bonds, the problem of insufficient electrocatalytic performance of perovskite oxides is solved, efficient furfural conversion is achieved, and the amount of precious metals is reduced.

CN119800436AActive Publication Date: 2025-04-11INNER MONGOLIA UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510279600.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-11
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

In the prior art, the electrocatalytic properties of perovskite oxides are limited by substrate adsorption capacity and number of active sites, and precious metal catalysts are costly and have limited resources, making them difficult to widely use.

Method used

By optimizing the concentration of the impregnation solution and controlling the calcining temperature, using physical adsorption and chemical adsorption, the Ru single atoms are anchored at the La defect position of the La0.9NiO3 perovskite oxide nanofiber to form a Ru-O bond, and a high catalytic activity is prepared.

Benefits of technology

In the electrocatalytic furfural C-C coupling reaction, the furfural conversion rate can reach 82%, while reducing the amount of precious metals and increasing the active site, improving the catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800436A_ABST
    Figure CN119800436A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a perovskite oxide nanofiber for anchoring Ru monatomic. The method comprises the following steps: 1) mixing a polyvinylpyrrolidone solution, La (NO3) 3.6 H2O and Ni (NO3) 3.6 H2O for 10 to 14 hours to obtain a spinning precursor solution; 2) performing electrostatic spinning on the spinning precursor solution to obtain a polyvinylpyrrolidone nanofiber membrane; the invention discloses a preparation method of Ru-La0. 9NiO3. The preparation method comprises the following steps: (1) preparing a polyvinylpyrrolidone nanofiber membrane, (2) dipping La0. 9NiO3 in a methanol solution of RuCl3, (3) calcining the polyvinylpyrrolidone nanofiber membrane to obtain La0. 9NiO3, (4) dipping La0. 9NiO3 in a methanol solution of RuCl3 to obtain Ru-dipped La0. 9NiO3, and (5) calcining the Ru-dipped La0. 9NiO3 to obtain Ru-La0. 9NiO3. The obtained nanofiber is used for electro-catalysis furfural reaction to generate 1, 2-bis (furan-2-yl) ethane-1, 2-diol (HDF), and the furfural conversion rate can reach 82%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic biomass conversion, and in particular to a preparation method and application of perovskite oxide nanofibers anchoring Ru single atoms. Background Art

[0002] Biomass energy is a renewable and sustainable resource in nature. It is rich in variety, widely distributed and low in cost. These advantages make it the most competitive substance to deal with energy shortages. Biomass compounds can be used as carriers for hydrogen storage and transportation. The electrocatalytic hydrogenation of organic matter is a promising technology for achieving efficient utilization and conversion of biomass compounds. Compared with thermal catalysis, electrocatalysis avoids high temperature and high pressure reaction conditions, reduces the use of additional hydrogen, has the advantages of being green and safe, and is in line with the sustainable development strategy.

[0003] Furfural can be obtained from agricultural and forestry wastes. Furfural is an important intermediate in the production of key furan compounds such as 5-hydroxymethylfurfural and furan resin. Furfuryl alcohol, 1,2-di(furan-2-yl)ethane-1,2-diol (HDF), tetrahydrofuran and other high value-added chemicals obtained by selective hydrogenation of furfural are widely used in the fields of energy, chemical industry and materials.

[0004] In the electrocatalytic method, precious metal catalysts (such as Pt, Ru and Pd) are one of the ideal catalysts with high catalytic activity and stability. However, due to the high cost of precious metals and limited resources, their wide application is restricted. Therefore, it is urgent to develop stable and effective electrocatalysts to replace precious metal catalysts. Although perovskite oxides have rich elemental composition and flexible and adjustable structure, their electrocatalytic performance still has many limitations, such as limited adsorption capacity for substrates and insufficient number of active sites. At present, although materials that anchor single atoms in oxides have been studied, materials that anchor precious metal single atoms in perovskite oxides have not yet been made. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of perovskite oxide nanofibers anchoring Ru single atoms in view of the limitations of the current technology. The method optimizes the concentration of the impregnation solution and uses physical adsorption to initially anchor Ru single atoms, and then further controls the calcination temperature and uses chemical adsorption to allow Ru single atoms to enter the defective sites of La to form Ru-O bonds, thereby finally obtaining La with Ru single atoms anchored. 0.9 NiO3 perovskite oxide nanofibers are used in the electrocatalytic furfural CC coupling reaction. The nanofibers obtained by the invention can achieve a furfural conversion rate of 82% in the electrocatalytic furfural reaction.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A method for preparing perovskite oxide nanofibers anchoring Ru single atoms comprises the following steps: 1) Mixing polyvinyl pyrrolidone (PVP) solution, La(NO3)3·6H2O and Ni (NO3)3·6H2O for 10-14 h to obtain a spinning precursor solution; Among them, the mass ratio of La(NO3)3·6H2O and Ni(NO3)3·6H2O is 0.56~0.60:0.41~0.45; The mass ratio of polyvinyl pyrrolidone solution and La(NO3)3·6H2O is 8~11:0.56~0.60.

[0007] 2) electrospinning the spinning precursor solution to obtain a polyvinyl pyrrolidone nanofiber membrane; The voltage of the electrospinning is 14-18 kV, and the spinning distance is 14-18 cm.

[0008] 3) The polyvinyl pyrrolidone nanofiber membrane is calcined to obtain La 0.9 NiO3; The calcination treatment includes a first calcination treatment and a second calcination treatment; in the first calcination treatment, the temperature is 200-280°C and the time is 2.5-4.5 h; in the second calcination treatment, the temperature is 750-840°C and the time is 1.5-3.5 h.

[0009] The rate of heating from room temperature to the first calcination temperature and the rate of heating from room temperature to the second calcination temperature in the calcination treatment are independently 5-8°C / min.

[0010] 4) The obtained La 0.9 NiO3 and RuCl3 were added to methanol and immersed for 8-16 hours, and then La impregnated with Ru was obtained. 0.9 NiO3; add 0.1~0.6 g of RuCl3 per 15 mL of methanol; 5) La impregnated with Ru 0.9 NiO3 is calcined to obtain Ru-La 0.9 NiO3, namely La anchoring Ru single atoms 0.9 NiO3 perovskite oxide nanofibers; The solvent of the polyvinyl pyrrolidone solution in step 1) is N,N-dimethylformamide (DMF), and the mass fraction of polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution is 8-12%.

[0011] Step 3) The first calcination treatment is carried out in a tube furnace with an argon atmosphere; the second calcination treatment is carried out in a muffle furnace.

[0012] Step 4) 0.9 The mass ratio of NiO3 to RuCl3 is 0.09~0.15:0.1~0.6.

[0013] Step 5) The calcination treatment comprises a one-step calcination treatment, during which the temperature is 300-380° C. and the time is 1.5-2.5 h.

[0014] Step 5) The rate of increasing the temperature from room temperature to the one-step calcination temperature is 4-6 °C / min.

[0015] Step 5) The calcination treatment is carried out in a tubular furnace with a nitrogen atmosphere.

[0016] The La anchoring Ru single atom prepared by the method 0.9 Application of NiO3 perovskite oxide nanofibers for electrocatalytic furfural CC coupling reaction to prepare HDF.

[0017] Specifically, the steps include: electrocatalysis for 1 to 10 hours in a single electrolytic cell and three-electrode system; wherein the reference electrode is an Ag / AgCl electrode, the counter electrode is graphite, and the working electrode is La loaded with anchored Ru atoms. 0.9 Hydrophilic carbon paper of NiO3 perovskite oxide nanofibers; Every 1cm 2 Hydrophilic carbon paper is loaded with 1~1.2 mg of La anchored Ru atoms. 0.9 NiO3 perovskite oxide nanofibers; the electrolyte is 10~100 mmol / L furfural in phosphate buffer.

[0018] The essential features of the present invention are: The La anchoring Ru single atom obtained by the present invention 0.9 NiO3 perovskite oxide nanofibers, combined with single-atom catalysts and perovskite oxide catalysts, reduce the amount of precious metals compared to single-atom catalysts and increase the active sites compared to perovskite oxide catalysts. First, the mass ratio of La(NO3)3·6H2O and Ni(NO3)3·6H2O in the electrospinning solution was controlled to prepare La(NO3)3·6H2O nanofibers with La defect sites. 0.9 NiO3 perovskite oxide nanofibers. Secondly, the RuCl3 and La 0.9The mass ratio of NiO3 is that if the concentration of RuCl3 solution is high, Ru clusters are easily formed on the surface of nanofibers; if the concentration of RuCl3 solution is low, it is not enough to anchor Ru in La defect sites. Finally, the calcination temperature is optimized to make Ru anchored in La 0.9 The La defect sites of NiO3 perovskite oxide form bonds with O to form a stable catalyst structure.

[0019] The beneficial effects of the present invention include: 1) The present invention uses an electrospinning method, an impregnation method and a high-temperature calcination method to prepare Ru-La perovskite oxide nanofibers anchoring Ru single atoms. 0.9 NiO3.

[0020] 2) The present invention provides an effective method to anchor the noble metal single atom Ru on La 0.9 The La defect site of NiO3 realizes the synergistic catalytic effect of noble metal single atoms and perovskite oxides, which is used for the electrocatalytic furfural CC coupling reaction to prepare HDF, and the furfural conversion rate can reach 82%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the La obtained in Example 1 0.9 Scanning electron micrograph of NiO3 perovskite oxide nanofibers.

[0022] Figure 2 is the Ru-La obtained in Example 1 0.9 Scanning electron micrograph of NiO3 perovskite oxide nanofibers.

[0023] Figure 3 This is a scanning electron microscope image of the material obtained in Example 2.

[0024] Figure 4 is the Ru-La obtained in Example 3 0.9 X-ray diffraction spectrum of NiO3 perovskite oxide nanofibers.

[0025] Figure 5 is the Ru-La obtained in Example 4 0.9 Transmission electron microscopy and elemental scanning images of NiO3 perovskite oxide nanofibers.

[0026] Figure 6 is the Ru-La obtained in Example 1 0.9 The conversion rate effect of NiO3 perovskite oxide nanofibers for electrocatalytic furfural reaction at different voltages.

[0027] Figure 7 is Ru-La in Example 1 0.9H NMR spectrum data of the product HDF obtained by electrocatalytic CC coupling reaction of furfural using NiO3 perovskite oxide nanofibers. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing a Ru-anchored perovskite oxide nanofiber, wherein the Ru-anchored perovskite oxide nanofiber is Ru-La 0.9 NiO3, including the following steps: 1) Mixing polyvinyl pyrrolidone solution, La(NO3)3·6H2O and Ni(NO3)3·6H2O to obtain a spinning precursor solution; 2) electrospinning the spinning precursor solution to obtain a polyvinyl pyrrolidone nanofiber membrane; 3) The polyvinyl pyrrolidone nanofiber membrane is calcined to obtain La 0.9 NiO3.

[0029] 4) La 0.9 NiO3 was impregnated in a methanol solution of RuCl3 to obtain La impregnated with Ru. 0.9 NiO3.

[0030] 5) La impregnated with Ru 0.9 NiO3 is calcined to obtain Ru-La 0.9 NiO3.

[0031] In the present invention, the solvent of the polyvinyl pyrrolidone solution in step 1) is preferably N,N-dimethylformamide (DMF), and the mass fraction of polyvinyl pyrrolidone (PVP) in the polyvinyl pyrrolidone solution is preferably 8-12%, more preferably 10%.

[0032] In the present invention, when the perovskite oxide nanofiber is La 0.9 In the case of NiO3, the mass ratio of La(NO3)3·6H2O to Ni(NO3)3·6H2O is preferably 0.57~0.59:0.42~0.44, and more preferably 0.58:0.43.

[0033] In the present invention, the mass ratio of the polyvinyl pyrrolidone solution to La(NO3)3·6H2O is preferably 9-11:0.57-0.59, more preferably 10:0.58.

[0034] In the present invention, the mixing time in step 1) is preferably 11 to 13 h, more preferably 12 h; the mixing temperature is preferably room temperature; and the mixing is preferably carried out under stirring conditions.

[0035] In the present invention, the voltage of the electrospinning in step 2) is preferably 15-17 kV, more preferably 16 kV; the spinning distance is preferably 15-17 cm, more preferably 16 cm.

[0036] In the present invention, the calcination treatment in step 3) preferably includes a first calcination treatment and a second calcination treatment; in the first calcination treatment, the temperature is preferably 240-250°C; the time is preferably 2.5-3.5 h, and more preferably 3 h; in the second calcination treatment, the temperature is preferably 770-820°C, more preferably 780-800°C; the time is preferably 2.5-3.5 h, and more preferably 3 h.

[0037] In the present invention, the rate of heating from room temperature to the first calcination temperature and the rate of heating from the first calcination temperature to the second calcination temperature are independently preferably 4-6°C / min, more preferably 5°C / min.

[0038] In the present invention, the first calcination treatment is preferably carried out in a tubular furnace with an argon atmosphere; the second calcination treatment is preferably carried out in a muffle furnace, and the process of heating from room temperature to the first calcination temperature is preferably carried out in an argon atmosphere.

[0039] In the present invention, La 0.9 NiO3 and RuCl3 were added to methanol for impregnation. 0.9 The mass ratio of NiO3 to RuCl3 is preferably 0.11-0.13:0.2-0.4, more preferably 0.12:0.3. The volume of methanol is preferably 12-18 mL, more preferably 15 mL; the immersion time is preferably 10-14 h, more preferably 12 h.

[0040] In the present invention, La impregnated with Ru 0.9 NiO3 is subjected to a one-step calcination treatment, in which the temperature is preferably 320-360°C, more preferably 340-350°C; the time is preferably 1.5-2.5 h, more preferably 2 h.

[0041] In the present invention, the rate of heating from room temperature to the one-step calcination treatment temperature is preferably 4-6 °C / min, more preferably 5 °C / min. The one-step calcination treatment is preferably carried out in a tubular furnace with a nitrogen atmosphere, and the process of heating from room temperature to the one-step calcination treatment temperature is preferably carried out in a nitrogen atmosphere.

[0042] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0043] Embodiment 1: 0.2923 gLa(NO3)3·6H2O and 0.2181 g Ni(NO3)3·6H2O were added to 5 g PVP solution (in PVP solution, the solvent was DMF and the mass fraction of PVP was 10%), and stirred at 400 rmp for 12 h at room temperature to obtain a uniformly mixed spinning precursor solution. The spinning precursor solution was electrospun at a voltage of 16 kV and a spinning distance of 16 cm to obtain a PVP nanofiber membrane with a thickness of about 1 mm. The PVP nanofiber membrane was placed in a tubular furnace for calcination. First, it was heated from room temperature to 250 ℃ at a rate of 5 ℃ / min in an argon atmosphere, calcined at 250 ℃ and argon atmosphere for 3 h, and then transferred to a muffle furnace and heated from 20 ℃ to 800 ℃ at a rate of 5 ℃ / min. It was kept at 800 ℃ for 3 h to obtain La 0.9 NiO3 perovskite oxide nanofibers. 0.12 g La 0.9 NiO3 perovskite oxide nanofibers and 0.3 g RuCl3 were added into 15 mL methanol solution and soaked for 12 h. The soaked material was calcined at 350 °C in nitrogen atmosphere for 2 h. Ru-La 0.9 NiO3 perovskite oxide nanofibers.

[0044] Embodiment 2: The mass of La(NO3)3·6H2O in Example 1 was changed to 0.2598 g, and the other conditions were the same as in Example 1. However, the target substance was not obtained.

[0045] Embodiment 3: The mass fraction of Ru in Example 1 was changed to 2.8%, and the other conditions were the same as in Example 1 to obtain Ru-La 0.9 NiO3 perovskite oxide nanofibers.

[0046] Embodiment 4: 0.2900 gLa(NO3)3·6H2O and 0.2170 g Ni(NO3)3·6H2O were added to 4.8 g PVP solution (in PVP solution, the solvent was DMF and the mass fraction of PVP was 12%), and stirred at room temperature at 400 rpm for 13 h to obtain a uniformly mixed spinning precursor solution. The spinning precursor solution was electrospun at a voltage of 15 kV and a spinning distance of 15 cm to obtain a PVP nanofiber membrane. The PVP nanofiber membrane was calcined. First, the temperature was raised from room temperature to 240 ℃ at a rate of 4.8 ℃ / min in an argon atmosphere, and calcined for 2.8 h. Then, it was transferred to a muffle furnace and heated from room temperature to 780 ℃ and calcined for 3 h to obtain La 0.9NiO3 perovskite oxide nanofibers. 0.13 g La 0.9 NiO3 perovskite oxide nanofibers and 0.31g RuCl3 were added to 15 mL methanol solution and soaked for 11 h. The soaked material was heated from room temperature to 340 °C at a rate of 4.8 °C / min under nitrogen atmosphere and calcined for 1.9 h. Ru-La 0.9 NiO3 perovskite oxide nanofibers.

[0047] Embodiment 5: This embodiment provides a method for electrocatalytic furfural CC coupling reaction, which is carried out according to the following steps: 15 mL of 50 mmol / L furfural in phosphate buffer (pH = 6.86) was added to the single electrolytic cell, and the electrochemical test was performed using the three-electrode system of Chenhua CHI760E electrochemical workstation, where the reference electrode was an Ag / AgCl electrode, the counter electrode was a graphite rod, and the working electrode was loaded with 1-1.2 mg / cm 2 Ru-La 0.9 The hydrophilic carbon paper with NiO3 catalyst was used. The reaction was carried out for 4 hours at a given voltage using the chronoamperometry method. The product was detected by gas chromatography, and the conversion rate of furfural was calculated to be 82% at -1.4 V vs. RHE.

[0048] Preparation of the working electrode: 3 mg Ru-La 0.9 NiO3, 340 µL pure water, 160 µL ethanol and 20 µL Nafion were mixed evenly and ultrasonicated for 5 min to obtain a uniformly mixed catalyst ink. 2 180 μL of the mixed catalyst ink was added onto the hydrophilic carbon paper to obtain a catalyst loading of 1.038 mg / cm 2 Working electrode.

[0049] Characterization results: The La obtained in Example 1 0.9 NiO3 perovskite oxide nanofibers were characterized by scanning electron microscopy. Figure 1 It can be seen that the present invention successfully prepared La 0.9 NiO3 perovskite oxide nanofibers.

[0050] The Ru-La obtained in Example 1 0.9 NiO3 perovskite oxide nanofibers were characterized by scanning electron microscopy. Figure 2 It can be seen that the present invention successfully prepared Ru-La 0.9 NiO3 perovskite oxide nanofibers.

[0051] The material obtained in Example 2 was characterized by scanning electron microscopy. Figure 3 It can be seen that the preparation of the target material was not successful. Due to the increase in the mass ratio of polyvinyl pyrrolidone solution and La(NO3)3·6H2O, the excess metal La could not enter the perovskite oxide lattice to form a stable structure. After calcination, polyvinyl pyrrolidone and other polymer compounds volatilized, resulting in morphological collapse and destruction of the nanofiber morphology.

[0052] The Ru-La obtained in Example 3 0.9 NiO3 perovskite oxide nanofibers were characterized by X-ray diffraction. Figure 4 It can be seen that the present invention successfully prepared Ru-La 0.9 NiO3 perovskite oxide nanofibers.

[0053] The Ru-La obtained in Example 4 0.9 NiO3 perovskite oxide nanofibers were characterized by transmission electron microscopy and element scanning tests. Figure 5 As shown in (a), the present invention successfully prepared Ru-La 0.9 NiO3 perovskite oxide nanofibers. Figure 5 From (bf) in the figure, we can see that the element scan diagram contains four elements: La, Ni, O and Ru.

[0054] The Ru-La obtained in Example 4 0.9 NiO3 perovskite oxide nanofibers were subjected to the test given in Example 5. Figure 6 It can be seen that the conversion rate of furfural reached 82% at -1.4 V vs. RHE.

[0055] Figure 7 The following is the H NMR spectrum of the product HDF. Figure 7 The winning bid corresponds to H in ad.

[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0057] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing perovskite oxide nanofibers anchoring Ru single atoms, characterized in that: The method comprises the following steps: 1) Mixing polyvinyl pyrrolidone solution, La(NO3)3·6H2O and Ni(NO3)3·6H2O for 10-14 h to obtain a spinning precursor solution; Among them, the mass ratio of La(NO3)3·6H2O and Ni(NO3)3·6H2O is 0.56~0.60:0.41~0.45; The mass ratio of polyvinyl pyrrolidone solution and La(NO3)3·6H2O is 8~11:0.56~0.60; 2) electrospinning the spinning precursor solution to obtain a polyvinyl pyrrolidone nanofiber membrane; The voltage of the electrospinning is 14-18 kV, and the spinning distance is 14-18 cm; 3) The polyvinyl pyrrolidone nanofiber membrane is calcined to obtain La 0.9 NiO3; The calcination treatment includes a first calcination treatment and a second calcination treatment; in the first calcination treatment, the temperature is 200-280°C and the time is 2.5-4.5 h; in the second calcination treatment, the temperature is 750-840°C and the time is 1.5-3.5 h; 4) The obtained La 0.9 NiO3 and RuCl3 were added to methanol and immersed for 8-16 hours, and then La impregnated with Ru was obtained. 0.9 NiO3; add 0.1~0.6 g of RuCl3 per 15 mL of methanol; 5) La impregnated with Ru 0.9 NiO3 is calcined to obtain Ru-La 0.9 NiO3, i.e., perovskite oxide nanofibers anchoring single Ru atoms.

2. The method for preparing the Ru single atom anchored perovskite oxide nanofiber according to claim 1, characterized in that: Step 1) The solvent of the polyvinyl pyrrolidone solution is N,N-dimethylformamide, and the mass fraction of polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution is 8-12%.

3. The method for preparing the Ru single atom anchored perovskite oxide nanofiber according to claim 1, characterized in that: Step 3) the first calcination treatment is carried out in a tube furnace with an argon atmosphere; the second calcination treatment is carried out in a muffle furnace; The rate of heating from room temperature to the first calcination temperature and the rate of heating from room temperature to the second calcination temperature in the calcination treatment are independently 5-8°C / min.

4. The method for preparing Ru single-atom anchored perovskite oxide nanofibers according to claim 1, characterized in that the steps 4) Medium 0.9 The mass ratio of NiO3 to RuCl3 is 0.09~0.15:0.1~0.

6.

5. The method for preparing the Ru single-atom anchored perovskite oxide nanofibers according to claim 1, characterized in that: Step 5) The calcination temperature is 300-380°C, the time is 1.5-2.5h; the heating rate is 4-6°C / min; the calcination treatment is carried out in a tubular furnace with a nitrogen atmosphere.

6. Application of the perovskite oxide nanofiber anchoring Ru single atoms prepared by the method of claim 1, characterized in that: Used for electrocatalytic furfural CC coupling reaction to prepare HDF.

7. The use according to claim 6, characterized in that: The method comprises the following steps: performing electrocatalysis for 1 to 10 hours in a single electrolytic cell and three-electrode system; wherein the reference electrode is an Ag / AgCl electrode, the counter electrode is graphite, and the working electrode is a hydrophilic carbon paper loaded with perovskite oxide nanofibers anchoring single Ru atoms; Every 1cm 2 The hydrophilic carbon paper is loaded with 1~1.2 mg of perovskite oxide nanofibers anchoring Ru single atoms; the electrolyte is 10~100 mmol / L furfural in phosphate buffer.

Citation Information

Patent Citations

  • Rare earth lanthanum doped nanometer TiO2 electrode and furfural electrocatalytic reduction method by using same

    CN103603008A

  • In-situ carbon template method for preparing porous perovskite LaFeO3 and application thereof

    CN109999819A

  • Orthorhombic phase P-doped La2Co2O5 perovskite nanofiber, electrocatalyst formed by same and preparation method

    CN112442760A

  • Pd-doped perovskite oxide nanofiber as well as preparation method and application thereof

    CN116550336A

  • Carbon nanofiber loaded monatomic copper catalyst as well as preparation method and application thereof

    CN116870908A